2010
DOI: 10.1080/01457631003689211
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Heat Conduction Models for Nanofluids

Abstract: The mechanism of heat transfer intensification recently brought about by nanofluids is analyzed in this article, in the light of the non-Fourier dual-phase-lagging heat conduction model. The physical problem involves an annular geometry filled with a nanofluid, such as typically used for measurements of the thermal conductivity with Blackwell's line heat source probe. The mathematical formulation for this problem is analytically solved with the classical integral transform technique, thus providing benchmark r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Therefore, if the viscosity is very high, there will be a penalty on the pumping power requirement to achieve the system's target. In the recent past, much research progress has been made on the thermal conductivity of nanofluids [22][23][24][25][26][27][28][29][30][31][32], which are a few of the copious works that can be found on theoretical and experimental reviews of the thermal conductivity of nanofluids. However, concerning the viscosity of nanofluids, very few theoretical models have been developed based on the unique properties of nanoparticles [2,33].…”
mentioning
confidence: 99%
“…Therefore, if the viscosity is very high, there will be a penalty on the pumping power requirement to achieve the system's target. In the recent past, much research progress has been made on the thermal conductivity of nanofluids [22][23][24][25][26][27][28][29][30][31][32], which are a few of the copious works that can be found on theoretical and experimental reviews of the thermal conductivity of nanofluids. However, concerning the viscosity of nanofluids, very few theoretical models have been developed based on the unique properties of nanoparticles [2,33].…”
mentioning
confidence: 99%
“…Many attempts have been made to formulate the effective thermal conductivity and dynamic viscosity of nanofluids [5][6][7][8]. Das et al [9] and Putra et al [10] have investigated a water-Al 2 O 3 suspension experimentally and found that by raising the Subscripts bf base fluid nf nanofluid p particle and solid phase nanofluid temperature, the effective thermal conductivity increases remarkably while the dynamic viscosity decreases.…”
Section: Introductionmentioning
confidence: 98%
“…Their results show that heat transfer mechanisms, such as phonon transport in the solid/liquid interface and electron transport, must be considered to estimate the exact thermal conductivity of nanofluid. The mechanism of heat transfer intensification, recently brought about by nanofluids is analyzed by Quaresma et al (2010) in the light of the non-Fourier dual-phase-lagging heat conduction model. The mathematical formulation for this problem is analytically solved with the classical integral transform technique, thus providing benchmark results for the temperature predicted with the dual-phase-lagging model.…”
Section: Introductionmentioning
confidence: 99%